2016
DOI: 10.1037/adb0000115
|View full text |Cite
|
Sign up to set email alerts
|

Poor body image and alcohol use in women.

Abstract: Two studies were conducted to examine the association between body image and alcohol use. Of interest was the extent to which alcohol outcome expectancies act as a moderator in this relationship, particularly in women. In Study 1, 421 college students (175 men, 246 women) provided self-report data on body image, social expressiveness expectancies, and average weekly alcohol use; the data were examined using a moderation model. Results showed that women with poor body image and high social expressiveness expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
2
12
0
5
Order By: Relevance
“…Estudos indicam que situações associadas a problemas de baixa autoestima decorrente da não aceitação das mudanças do próprio corpo levam os adolescentes a predisposição ao uso e abuso de drogas (Holzhauer, Zenner, & Wulfert, 2015;Santos & Santos, 2002). Ao se verificar os padrões de consumo de substancias entre os adolescentes, este trabalho indicou que o uso experimental de substancias é alto, independentemente do nível de satisfação corporal dos adolescentes.…”
Section: Discussionunclassified
“…Estudos indicam que situações associadas a problemas de baixa autoestima decorrente da não aceitação das mudanças do próprio corpo levam os adolescentes a predisposição ao uso e abuso de drogas (Holzhauer, Zenner, & Wulfert, 2015;Santos & Santos, 2002). Ao se verificar os padrões de consumo de substancias entre os adolescentes, este trabalho indicou que o uso experimental de substancias é alto, independentemente do nível de satisfação corporal dos adolescentes.…”
Section: Discussionunclassified
“…This difference may not be statistically significant because of the small sample of our study. In a study on 175 male and 246 female alcoholics, higher alcohol abuse rates were found in women with low body image scores than men [13]. It can be said that the relationship between substance dependence and body perception is bidirectional.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol and substance addicts have lower body image scores [13]. Alcohol and substance use may emerge in order to alleviate the anxiety arising from impairment of body image [14].…”
Section: Introductionmentioning
confidence: 99%
“…As noted before, only one study has examined alcohol expectancies in the link between body image concerns and alcohol use in university students (Holzhauer et al, 2016). However, the generalizability of the study's findings is limited for a number of reasons including (a) the use of a female-only sample (in Study 2), (b) the operationalization of body image concerns was solely based on weight and shape, and (c) the examination of only one specific alcohol-related expectancy (i.e., social expressiveness).…”
Section: Present Study and Aimsmentioning
confidence: 99%
“…Holzhauer, Zenner, and Wulfert (2016) found that university women with poor body image and a high level of social expressiveness, a positive alcohol expectancy (PAE) that alcohol will improve functioning in social situations, had a higher weekly alcohol consumption rate and drank more alcohol during a mock tasting experiment, compared to women with poor body image but a lower level of social expressiveness. Holzhauer, Zenner, and Wulfert (2016) found that university women with poor body image and a high level of social expressiveness, a positive alcohol expectancy (PAE) that alcohol will improve functioning in social situations, had a higher weekly alcohol consumption rate and drank more alcohol during a mock tasting experiment, compared to women with poor body image but a lower level of social expressiveness.…”
mentioning
confidence: 99%